Nanofluids Application in the Drilling Process - Shalimba, Veikko; Sopko, Bruno (Manufacturing Technology Journal, 2018)
A high performance of heat transfer fluid has a great influence on the size, weight and cost of heat transfer systems, therefore a high-performance heat transfer fluid is very important in many industries. Over the last decades nanofluids have been developed. According to many researchers and publications on nanofluids its evident that nanofluids are found to exhibit enhance thermal conductivity. The aim of this experiment was to investigate the change of workpiece temperature during drilling using Jatropha oil with nanoparticle and water with iron nanoparticle as lubricating and cooling fluids. These experiments were carried out with samples of nanofluid with different volume ratio. Samples JN1, JN5 and JN10 of iron nanoparticles in the base Jatropha oil with iron volume fraction 1%, 5% and 10% respectively. Samples WN1, WN5 and WN10 of iron nanoparticles in the base water with iron volume fraction 1%, 5% and 10% respectively. The work arises from the projects which were realized at University J. E. Purkyne, Faculty of Mechanical Engineering, in cooperation with Namibia University of Science and technology, department of Mechanical Engineering.
Keywords: Jatropha oil; nanofluids; nanoparticles; temperature; drilling